A Conceptual Framework for Developing the Next Generation of Marine OBservatories (MOBs) for Science and Society - Crise, Alessandro; Ribera d’Alcalà, Maurizio; Mariani, Patrizio; Petihakis, George; Robidart, Julie; Iudicone, Daniele; Bachmayer, Ralf; Malfatti, Francesca (Frontiers in Marine Science, 2018)
In the field of ocean observing, the term of ‘observatory’ is often used without a unique meaning. A clear and unified definition of observatory is needed in order to facilitate the communication in a multidisciplinary community, to capitalize on future technological innovations and to support the observatory design based on societal needs. In this paper, we present a general framework to define the next generation Marine OBservatory (MOB), its capabilities and functionalities in an operational context. The MOB structure has four components (observatory infrastructure, cyberinfrastructure, human capacity and knowledge generation engine) that are constantly and adaptively interacting with each other. Therefore, MOB is a complex infrastructure focused on a specific geographic area with the primary scope to generate knowledge via data and information thus addressing scientific, societal and economical challenges. MOB long-term sustainability, is a key feature that should be guaranteed by strategic planning that incorporates governance feedbacks. Innovations and the overall reduced-cost of equipment and operations will allow the development in quality and quantity of the MOBs globally. Thanks to the desirable MOB’s proliferation, a deeper biological understanding of the marine ecosystem should be reached thus contributing to effective conservation of ecosystems and management of humankind activities in the oceans. In sum, we provide an actionable blue-print for the upgrade and development of a sustained marine observatory producing knowledge to support science-based economical and societal decisions.